Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2025)
:Table of Content• A teaching program based on experiential learning and its effectiveness in developing strategic competence and productive thinking in the mathematics curriculum among sixth-grade students in HailDr. Howishel Saud Alhowishel• The Role of Incentives Used by Teachers on the Achievement of Autistic Students in East Jerusalem Schools from Teachers' PerspectiveMs. Nancy Mohammed Abdelsalam Issa , Ms. Amal Sami Ahmad Abdel-Rabu• The Degree of Use of Digital Content Design Applications by College of Humanities Students  in the Distance Learning and Teaching Strategies CourseMs. Nouf Farhan Alenazi , Ms. Nada AbdulAziz Al-Mashouq ,Prof. Mona Abdullah Al-Bisher• The Reality of Implementing Voluntary Hours in the Tracks System in Secondary Schools in the Northern Border Region from the Students’ Perspective and Its Impact on Their Career MaturityMr. Talal Glub Alshammary , Prof. Fahd Abdul-Aziz Abanmi• The effectiveness of employing digital games on First-Grade Students’ Achievement improving  the academic achievement of first-grade students in mathematics and enhancing their motivation to learn. Qualitative Study from parents’ perspectivesMs. Anan Shaker Hamdan• The Extent to Which Social Studies Teachers Employ Lateral and Design Thinking  in Architectural Education: An Exploratory Study from Their PerspectiveDr. Zouwaina Khalaf Al-Ghawi, Dr. Noor Ahmed Al Najar• Insights into the Reflection of Oman Vision 2040’s Priorities and Strategic Directives in the Newly Introduced ELT Textbook Series “Team Together Oman”: Content Analysis and Teachers’ PerspectivesMs. Salama Saif Hamed Al-Siyabi, Ms. Khadija Mohammed Nasser Al-Harthi
Keywords: Journal of Curriculum and Teaching Methodology